Non-heme-iron-mediated selective halogenation ofuUnactivated carbon-hydrogen bonds - Bleher, Katharina; Comba, Peter; Faltermeier, Dieter; Gupta, Ashutosh; Kerscher, Marion; Krieg, Saskia; Martin, Bodo; Velmurugan, Gunasekaran; Yang, Shuyi (Chemistry - a European journal, 2022)
Oxidation of the iron(II) precursor [(L1)FeIICl2], where L1 is a tetradentate bispidine, with soluble iodosylbenzene (sPhIO) leads to the extremely reactive ferryl oxidant [(L1)(Cl)FeIV=O]+ with a cis disposition of the chlorido and oxido coligands, as observed in non-heme halogenase enzymes. Experimental data indicate that, with cyclohexane as substrate, there is selective formation of chlorocyclohexane, the halogenation being initiated by C−H abstraction and the result of a rebound of the ensuing radical to an iron-bound Cl−. The time-resolved formation of the halogenation product indicates that this primarily results from sPhIO oxidation of an initially formed oxido-bridged diiron(III) resting state. The high yield of up to >70 % (stoichiometric reaction) as well as the differing reactivities of free Fe2+ and Fe3+ in comparison with [(L1)FeIICl2] indicate a high complex stability of the bispidine-iron complexes. DFT analysis shows that, due to a large driving force and small triplet-quintet gap, [(L1)(Cl)FeIV=O]+ is the most reactive small-molecule halogenase model, that the FeIII/radical rebound intermediate has a relatively long lifetime (as supported by experimentally observed cage escape), and that this intermediate has, as observed experimentally, a lower energy barrier to the halogenation than the hydroxylation product; this is shown to primarily be due to steric effects.
Gesehen am 04.01.2023